Electronic health records and decision support local and global perspectives - Neves, José (2008)
Safer, less expensive, and higher-quality health care can be achieved using clinical decision support (CDS), although the use of CDS often leads to disappointing results. Various problems and limitations can be pointed being the most frequently referred by the physicians the inadequate implementation of the clinical workflow. Electronic Health Records (EHR) and Patient Health Record Systems (PHRS) can play an important role in CDS mitigating those limitations and enabling the effective use of the archived information in the support of the clinical practice and generating the right knowledge to make decisions. The availability of such knowledge is crucial either, for the hospitals and for the government institutions. This brings new requirements for the EHR and PHRS conception and for the use of the information out of the boundaries of the hospitals and health centers. Interoperation and open models constitute the greater challenges that EHR enfaces in the very next future. This paper presents a survey on the design, development and implementation of PHRS in terms of organizational, regional, national and worldwide initiatives. Finally is presented the EHR implementation in the Hospital Geral de Santo António, EPE, one of the major hospitals in the North Region of Portugal.